Ichnology of the Late Carboniferous Hoyada Verde Formation of western Argentina: Exploring postglacial shallow-marine ecosystems of Gondwana - Alonso Muruaga, Pablo Joaquin (2013)
The postglacial interval of the Upper Carboniferous Hoyada Verde Formation of western Argentina contains an ichnofauna dominated by Psammichnites plummeri and Psammichnites implexus, with minor occurrences of Ptychoplasma vagans, Treptichnus bifurcus, Lingulichnus verticalis, Protovirgularia isp., Lockeia isp., Palaeophycus isp., scarce arthropod trackways and some bilobate structures. The particular features of this association indicate a depauperate expression of the Cruziana Ichnofacies, and suggest a context that differs from the expected in normal shallow-marine settings (i.e. archetypal Cruziana Ichnofacies). Integration of sedimentologic, ichnologic, sequence-stratigraphic and paleontologic data points to a prograding deltaic system influenced by wave action. Trace fossils have been extensively used to recognize stressed brackish-water environments in the late Paleozoic of Gondwana. However, the recognition of stressed settings needs to take into consideration the specific paleogeographic context of glacially influenced Gondwanan settings. A postglacial open sea adjacent to a paleotopographic high is considered as a possible scenario for the Hoyada Verde Formation. In this particular setting, coastal biotas could have been influenced to some degree by the salinity gradient triggered by freshwater release near to melting ice masses stored in highlands and also by freshwater plumes due to longshore currents. Regional factors (e.g. proximity to highlands and climate) may have played an important role in controlling the characteristics of Gondwanan ichnofaunas. This suggests that the distinction between normal-marine and brackish-water settings in glacially influenced environments using trace fossils may not be as straightforward as in non-glacial settings.